(untitled) (Web of Teachers: Inderscience Research, 2024)
The orientation of special physical training in boxing practice is closely related to the technical and tactical variety of combat methods performed at different amplitudes, at different speeds and forces, in unusual situations. Depending on this situation, special physical training is aimed at solving the task of developing a wide range of physical qualities that allow successful competition fights. The following materials are required to be included in the training of training groups of all levels during the entire academic year, however, the size and intensity of the specified exercises are selected depending on the level of training of the trainees and the level of technical and tactical preparation of the trainees. In this article, we will consider how using games in boxing sports training can help students develop their physical qualities during training.